STUDENT SCIENTIFIC SOCIETIES AND THE YOUNG SCIENTISTS’ ASSOCIATION AT THE SAMARKAND STATE MEDICAL INSTITUTE (1960–1990) - qizi, O‘rinboyeva Malikabonu Ulug‘bek; qizi, Suyunova Roziya A’zam (Research Focus International Scientific Journal, 2026)
This article analyzes the formation, development, and role of student scientific societies and the Young Scientists’ Association at the Samarkand State Medical Institute during 1960–1990. The study examines student research circles, scientific conferences, seminars, and mechanisms for training young researchers. It also highlights the contribution of these organizations to the development of scientific thinking, research skills, and professional competencies in the field of medicine. The findings show that these scientific communities played a crucial role in the formation of scientific schools, the training of academic personnel, and the advancement of medical science within the institute.